Socio-demographic and maternal risk factors of malaria among pregnant women attending ante-natal care in Zamfara State, Nigeria - K., Hadiza; H., Abdul Rahman; K. S., Hayati; U. G., Ismaila (Madridge Publishers, 2018)
Malaria is a major global health concern. It is one of the world’s most prevalent serious infectious diseases, with approximately 250 million cases and one million deaths per year. The aim of this study is to determine the socio-demographic and maternal risk factors associated with malaria among pregnant women attending ante-natal care in Zamfara State, Nigeria. An unmatched case control study was conducted among pregnant women attending ante-natal care in Zamfara State, Nigeria. A total of 581 pregnant women both cases and controls were obtained using multistage random sampling. Cases and controls were defined as pregnant women attending ante-natal care from the selected general hospitals in Zamfara State, confirmed with and without malaria respectively, using Giemsa staining method based on their medical records. Face to face interview and self-administered pretested questionnaire in English and Hausa languages were used to obtain information on socio-demographic characteristics and maternal history of the respondents from May to August 2014. Data was analysed using SPSS version 21, using simple descriptive and multivariate logistic regression were employed to determine the predictors of malaria. The overall response rate was 89.8%. Pregnant women ≤ 25 years of age (AOR = 1.695, 95% CI = 1.031, 2.789, p = 0.038), informal education (AOR = 9.390, 95% CI = 5.516, 15.985, p < 0.001), unemployed (AOR = 25.948, 95% CI = 14.831, 45.398, p < 0.001) and first trimester (AOR = 1.856, 95% CI = 1.126, 3.060, p 0.015) were the risk factors. This study has identified the risk factors of malaria in Zamfara State, Nigeria. The findings in this study can be used by policy makers in planning how to tackle the factors associated with malaria among pregnant women in Zamfara State.